Experimental ice drilling with organosilicon fluid using the KEMS-135 drill in borehole 5G (Vostok Station, Antarctica) - Aleksei V. Bolshunov; Sergei A. Ignatev; Danil V. Serbin; Aleksei V. Turkeev (Записки Горного института, 2025)
The article presents the results of experimental drilling of congelation ice in the branch hole 5G-5 at the Vostok Station (Antarctica) using the KEMS-135 coring drill in the PMS-3 organosilicon fluid. The studies were conducted during the 70th Russian Antarctic Expedition and were aimed at assessing the technology efficiency in deep glacier drilling and opening of subglacial reservoirs, as well as at determining rational drilling parameters. Borehole preparation included extraction of drilling fluid, a body of geophysical studies, and wellbore reaming. The PMS-3 was delivered to the bottomhole using a specialized device called “Slonik”. Experimental drilling of congelation ice was conducted by the KEMS-135 coring drill. Two drilling runs were performed with core sampling of 1.10 and 1.14 m long, drilling depth 3595.15-3597.39 m. The presence of PMS-3 at the bottomhole was monitored by geophysical studies and sampling. Particular attention was given to analysing drilling modes, including mechanical speed, cuttings properties, and the effect of PMS-3 on the drilling equipment elements. The results of experimental drilling showed an increase in the mechanical drilling speed in the PMS-3 organosilicon fluid environment by 15-20 % compared to the used drilling fluid (kerosene + dichlorofluoroethane), as well as the absence of crown plugging and improved lubricating properties of the fluid. The article describes the promising areas of further research related to the drill design optimization for operation in the PMS-3 environment and the study of the long-term impact on subglacial ecosystems.